2009
DOI: 10.1111/j.1524-4741.2009.00842.x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and Predictive Factors, Treatment and Clinical Behavior of Palpable versus Nonpalpable Breast Cancer

Abstract: Potential contributions to these observed reduction come from primary prevention, chemoprevention, screening (secondary prevention), improved therapy (tertiary prevention), or combination of these. Nevertheless, approximately 10-15% of patients with breast cancer has an aggressive disease and develops distant metastases within 3 years after diagnosis of primary tumor (1). The risk of metastasis development increases directly with the presence of lymph node metastasis, a larger size of primary tumor and loss of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Prior studies suggest that, compared with nonpalpable tumours, palpable tumours might represent disease that is inherently more aggressive; however, the relative benefit of rt in the two groups of women was not assessed 4,5 . Tafra et al 5 found that, compared with mammography-detected tumours (n = 120), palpable tumours (n = 225) were larger (2 cm vs. 1 cm, p < 0.001) and more likely to be node-positive (46% vs. 19%, p < 0.01).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Prior studies suggest that, compared with nonpalpable tumours, palpable tumours might represent disease that is inherently more aggressive; however, the relative benefit of rt in the two groups of women was not assessed 4,5 . Tafra et al 5 found that, compared with mammography-detected tumours (n = 120), palpable tumours (n = 225) were larger (2 cm vs. 1 cm, p < 0.001) and more likely to be node-positive (46% vs. 19%, p < 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…The rates of local recurrence after breast-conserving therapy were similar for women with palpable and nonpalpable tumours, but the study was likely underpowered for assessment of recurrence outcomes. In another cohort of 649 women, palpable breast tumours were, compared with mammography-detected cancers, larger, higher grade, more likely to be node-positive, and more likely to be er-negative 4 . Although women with palpable tumours received more aggressive systemic and surgical therapies, they were still more likely than their counterparts with nonpalpable disease to experience a recurrence (24% vs. 11%) 4 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations